Characterization and in-vitro activity of powder metallurgy magnesium-zinc/ bioglass composite for biomedical applications - Mohd Amin Farhan Zaludin (School of Materials Engineering, Universiti Malaysia Perlis, 2015)
The purpose of this study is to investigate th effect of bio-glass addition into the composite in term of density, compressive strength, corrosion resistance and bioactivity and selection of proper amount of bio-glass so that the newly formed composite will have matched properties with those natural human bones.